PEMAHAMAN JODOUSHI SOUDA PADA MAHASISWA PENDIDIKAN BAHASA JEPANG UNIVERSITAS RIAU ANGKATAN 2021 - Aulia, Della; Nimashita, Hana; Widiati, Sri Wahyu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: This research is quantitative research. The purpose of this study is todetermine the level of understanding of Japanese Language Education students at RiauUniversity class of 2021 regarding the use of jodoushi souda. The population in thisstudy were students of the Japanese Language Education Study Program, University ofRiau, class of 2021 with a sample of 30 students. There are three indicators used in thisstudy to achieve the research objectives, they are (1) classifying, (2)inference/concluding, and (3) interpretation/interpreting. The results of this study arethat students' understanding of the use of jodoushi souda as denbun is in the lowerqualification with an average score of 44.33. Meanwhile, jodoushi souda as youtai isalso in the lower qualifications with an average score of 51.76. So, it can be concludedthat students' understanding of the use of jodoushi souda when viewed from the averagescore, souda as youtai is higher than souda as denbun.Keywords: Jodoushi, souda, youtai, denbun